Hubungan antara Diabetes Mellitus Gestasional dan Berat Badan Lahir dengan Kejadian Respiratory Distress Syindrom pada Neonatus di RSU Bina Kasih Tahun 2022 - Rotua Lenawati Tindaon; Jamalini Putri Tampubolon; Laura Shafarina; Larasati Larasati; Dewi Sartika Munthe (Universitas Batanghari Jambi, 2023)
Respiratory Distress Syndrome (RDS) is an acute and severe lung disease that affects infants, especially in preterm infants, where the infant's respiratory system is unable to perform gas exchange normally without assistance. The purpose of this study was to determine the relationship between gestational diabetes mellitus and birth weight with the incidence of respiratory distress syndrome in neonates at Bina Kasih General Hospital in 2022. This research method used an analytical survey with a cross sectional approach. The population in this study were all neonates with the incidence of Respiratory Distress Syndrome in July at Bina Kasih General Hospital in 2022 totaling 39 respondents. The sample of this study used the total population technique. Data collection uses primary data and secondary data. The data analysis technique is using the Chi-Square Test. The results obtained from data analysis using the chi-square test showed that from 39 respondents, there were 12 respondents (30.8%) who had gestational diabetes mellitus where all neonates with gestational diabetes mellitus experienced Respiratory Distress Syndrome and 18 respondents (46 ,2%) neonates with low birth weight where the majority experienced Respiratory Distress Syndrome, namely 13 respondents (33.3%). so it can be concluded that there is a relationship between gestational diabetes mellitus and birth weight with the incidence of respiratory distress. Syndrome in Neonates at Bina Kasih General Hospital in 2022.